HPV‐genotypes in high‐grade intraepithelial cervical lesions in Danish women. (1st June 2013) - Kirschner, Benny; Schledermann, Doris; Holl, Katsiaryna; Rosenlund, Mats; Raillard, Alice; Quint, Wim; Molijn, Anco; Jenkins, David; Junge, Jette
Abstract Objective A study was undertaken to assess the distribution of high‐risk HPV‐genotypes in high‐grade cervical intraepithelial neoplastic lesions in Danish women. Design Observational, cross‐sectional. Setting Danish data from a multi‐centre study undertaken in 13 European countries. Population 290 archived fixed biopsies with high‐grade cervical lesions from the Departments of Pathology at the University Hospitals in Hvidovre and Odense, Denmark. Methods Relevant histological samples were anonymized and shipped to a central laboratory for histopathology review and PCR‐testing for HPV‐DNA. A standardised HPV‐test methodology was utilised to enable comparison of HPV‐genotype distribution. Results Of 290 Danish cervical samples, 276 were evaluated as histologically adequate and all of these were HPV‐positive (HPV+). Of the HPV+ samples 77.9% were diagnosed with a single HPV‐type, with cervical intraepithelial neoplasia (CIN)3 diagnosed in 82.3% and CIN2, CIN2/3, adenocarcinoma in situ (AIS) and AIS+ other high‐grade lesion diagnosed in the remaining 17.7%. The most prevalent HPV‐types were: HPV16 (54.0%), HPV33 (13.5%), HPV31 (10.7%), HPV18 (7.9%) and HPV52 (4.7%). Of the HPV+ samples, 21.4% were diagnosed with multiple HPV‐types, with CIN3 diagnosed in 79.6% and CIN2, CIN2/3, AIS and AIS+ other high‐grade lesion diagnosed in the remaining 20.4%. The most prevalent HPV‐types were: HPV16 (49.2%), HPV31 (30.5%), HPV52 (27.1%), HPV51 (20.3%), HPV18 (16.9%), HPV33 (13.6%), HPV45 (11.9%), with 0.7% unknown types. Conclusions HPV16 and HPV18 were detected in approximately 75% of high‐grade intraepithelial cervical lesions in a Danish population (single or multiple infections); these two genotypes are considered causative in at least 61.9% of the high‐grade intraepithelial lesions (single infection).